UJI TOKSISITAS AKUT FRAKSI N-HEKSAN EKSTRAK METANOL DAUN DAN BATANG Impatiens balsamina Linn. DENGAN PEDOMAN OECD 425 - Benny Wijaya Sunggono; Indri Kusharyanti; Siti Nani Nurbaeti (Majalah Obat Tradisional, 2014)
Garden balsam (Impatiens balsamina Linn) is a plant that has been used for joint pain, insect bite, promotes regular menstrual cycle and prevents stomach cancer. Traditionally, the leaves of garden balsam are suspected to contain poison that can affect the digestive system. The purpose of this research is to evaluate the safety of the garden balsam stem and leaf n-hexane fraction so it can be used safely. Stem and leaf Methanol extract of garden balsam was fractioned into n-hexane fraction with liquid extraction method. Phytochemical screening showed that the fraction contains triterpenoid steroid compound. The OECD Guideline no 425: Acute Oral Toxicity (Up and Down Procedure) was adopted to evaluate the safety of the fraction. Two until three months old female Sprague Dawley rat were subjected to n-hexane fraction suspension. Limit test showed that the n-hexane fraction LD50 is greater than 5000 mg/kgBW. There were no clinical sign of toxicity on the eye, respiration system, behavior, autonomic and somatomotoric system up to dose 5000 mg/kgBW. At that dose, the fraction did not cause mortality on rats, and did not lower the body weight, food and water consumption of rats. The fraction also did not cause any histology change to the liver and renal. Our conclusion is the fraction is safe to consume below 5000mg/kgBW. According to Loomis classification, n-hexane fraction of garden balsam steam and leaf has low toxicity.